Inovasi Bomb Fizzies Antifeedant Dari Ekstrak Daun Pangi (Pangium edule Reinw.) Untuk Pengendalian Hama Kubis Plutella xylostella L. - Monika Sitohang; Juliet M. Eva Mamahit; Sandra E. Pakasi (Jurnal Agroekoteknologi Terapan, 2022)
Cabbage is a horticultural crop that has the potential to be developed in increasing national economic growth. One of the main pests of cabbage is Plutella xylostella. Plutella xylostella attacks cause up to 90% damage. Pangi (Pangium edule) is one of the plants that can be used as a vegetable pesticide in controlling P. xylostella pests.Pangium edule is a plant that can use as an alternative for P. xylostella pest control because it contains secondary metabolites which function as an antifeedant. The uniqueness of the antifeedant action which can inhibit the eating process of target organisms is very prospective in an ecological approach to agriculture. The purpose of this paper is to explore the potential of pangi as an innovative antifeedant bomb fizzies antifeedant for P. xylostella pest control in cabbage. The method that is used is the virtual method through the collection of literature studies then evaluated and made a summary. Bomb Fizzies Antifeedant is an idea inspired by natural camphor and then added with the pangi leaf extract as an antifeedant.Keywords: Cabbage, Plutella xylostella, Pangium edule, Bomb Fizzies AntifeedantAbstractKubis merupakan tanaman hortikultura yang berpotensi untuk dikembangkan dalam meningkatkan pertumbuhan perekonomian nasional. Salah satu hama utama kubis adalah hama Plutella xylostella. Serangan Plutella xylostella menyebabkan kerusakan hingga 90%. Pangi (Pangium edule) merupakan salah satu tanaman yang dapat digunakan sebagai pestisida nabati dalam mengendalikan hama P. xylostella.Pangium edule merupakan salah satu tanaman yang dapat digunakan sebagai alternatif pengendalian hama P.xylostella karena mengandung alkaloid, flavonoid, saponin, tanin dan terpenoid yang berfungsi sebagai antifeedant. Mekanisme kerja dari senyawa antifeedant adalah menghambat proses makan organisme target.Hal tersbut sangat pendekatan ekologi pada bidang pertanian. Tujuan dari penulisan ini yaitu untuk menggali potensi pangi sebagai inovasi bomb fizzies antifeedant untuk pengendalian hama P. xylostella pada tanaman kubis. Metode yang digunakan yaitu dengan virtual method melalui pengumpulan studi pustaka kemudian dievaluasi dan dibuat ringkasan . Bomb Fizzies Antifeedant merupakan ide yang terinspirasi dari kapur barus alami yang kemudian ditambahkan dengan penambahan ekstrak daun pangi sebagai antifeedant.Kata kunci: Kubis, Plutella xylostella, Pangium edule, Bomb Fizzies Antifeedant